2022
DOI: 10.21203/rs.3.rs-1677222/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on the interaction mechanism between Crocus sativus and Fusarium oxysporum based on dual RNA-seq

Abstract: Fusarium oxysporum is a widely distributed soil-borne fungus, which is the most serious pathogen in Crocus sativus production. Due to the lack of resistant cultivars of saffron,and the unclear disease resistance and pathogenic mechanism, there is no really effective control method at present. In this study, the process of F.oxysporum infection of saffron corms and the physiological responses of saffron were analyzed. On this basis, dual RNA-seq was performed on the saffron corms inoculated on the 3th and 6th d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…In addition, nematodes and rodents have also been reported to attack the corms and cause injury ( Khan and Sharma, 2020 ). Some researchers have reported the infection without injury and by just dipping the corm or germinated roots in the spore suspension ( Palmero et al., 2014 ; Gupta et al., 2020 ; Mirghasempour et al., 2022b ) but the present study and others have reported the infection after injuring the corm artificially ( Gupta and Vakhlu, 2015 ; Wani et al., 2016 ; Wani et al., 2018 ; Zhang et al., 2020 ; Bhagat et al., 2022 ; Luo et al., 2022 ). There are many reports on other plants wherein the screening for pathogenicity is done by injury such as cork oak ( Luque et al., 2000 ), kiwi fruit ( Di Marco et al., 2004 ), grape vines ( Halleen et al., 2007 ), Dendrobium nobile , and Dendrobium officinale ( Sarsaiya et al., 2020 ), potato ( Azil et al., 2021 ).…”
Section: Discussioncontrasting
confidence: 62%
“…In addition, nematodes and rodents have also been reported to attack the corms and cause injury ( Khan and Sharma, 2020 ). Some researchers have reported the infection without injury and by just dipping the corm or germinated roots in the spore suspension ( Palmero et al., 2014 ; Gupta et al., 2020 ; Mirghasempour et al., 2022b ) but the present study and others have reported the infection after injuring the corm artificially ( Gupta and Vakhlu, 2015 ; Wani et al., 2016 ; Wani et al., 2018 ; Zhang et al., 2020 ; Bhagat et al., 2022 ; Luo et al., 2022 ). There are many reports on other plants wherein the screening for pathogenicity is done by injury such as cork oak ( Luque et al., 2000 ), kiwi fruit ( Di Marco et al., 2004 ), grape vines ( Halleen et al., 2007 ), Dendrobium nobile , and Dendrobium officinale ( Sarsaiya et al., 2020 ), potato ( Azil et al., 2021 ).…”
Section: Discussioncontrasting
confidence: 62%